Epidemics and food systems: What gets framed, gets done - Gillespie, Stuart (Springer, 2020)
This brief article aims to interrogate some widely used concepts in framing the interactions between disease epidemics, food systems and nutrition, with a particular focus on the COVID-19 crisis. How should we conceptualize vulnerability in such situations – both with regard to viral exposure and to subsequent nutrition-relevant impacts of epidemics and responses (including lockdowns)? Is it possible to simultaneously pursue strategies aimed at strengthening resilience and driving transformation (‘building back better’)? What type of framing and conceptualization can help illuminate entry points and options for responding effectively to interacting crises? In addressing these questions, it’s important to re-visit lessons from past attempts to address the impacts of epidemics on food and nutrition security.